Analysis of the immune response of infected bovines with anaplasma marginale. Identification of infection stage marker antigens - Giardina, Salvatore; Hartt, Yamilet; Pance, Alena (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
It is hypothesized the existence of marker antigens capable to define early (acute phase) or late (convalescent phase) infection course with Anaplasma marginale. Five parasitologically free hybrid calves were splenectomized and experimentally infected with a Zulia isolate of Anaplasma marginale. Sera samples were collected before inoculation and during the overall period of the infection. The course of infection was followed through Giemsa stained blood smears and by packed cell volume (PCV). The period of infection was divided into the prepatent phase in which no apparent infection was evident, an acute phase in which a rapid increase of the parasitemia and the hematocrit reduction were conspicuous and a convalescent phase subjectively considered as a marked decrease in parasitemia, after treatment of the infected anumals with Oxytetracycline. Western blot assays and immunoplo analyses were performed. The frequency analysis of the detected antigens showed that some of them reacted with normal or prepatent sera, being non-specific cross reaction. Band 63 (p65 kDa) was specific in the acute phase. Bands 188; 68 (p70 kDa) and 58 (p60 kDa) were recognized mainly in the late or convalescent phases. These results also showed that band 18 (p19 or MSP5) was a marker for specific infection with Anaplasma.